Pengaruh Komitmen Organisasi Dan Karakteristik Pekerjaan Terhadap Organizational Citizenship Beharvior (OCB) PT. Telkom Akses Sukabumi - Repita Pitriani; Kokom Komariah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine whether organizational commitment, job characteristics have an influence on organizational citizenship beharvior on employees of PT Telkom Akses Sukabumi. The research method used is quantitative method with descriptive approach and associative analysis. The sample in this study amounted to 95 respondents who were employees of PT Telkom Akses Sukabumi by using purposive sampling technique. Data were obtained through a research questionnaire distributed to all samples containing 37 questions about organizational commitment variables, job characteristics and organizational citizenship beharvior, using a semantic differential measurement system. Furthermore, the data obtained with various tests to answer the hypothesis in this study. The results of this study indicate that there is a positive and significant influence between job characteristics variables on organizational citizenship beharvior and overall organizational commitment and job characteristics can improve organizational citizenship beharvior behavior in employees of PT Telkom Akses Sukabumi.